Dimensi-dimensi Kepemimpinan Transformatif Pendidikan Islam - Luluk Indarti (Ta'allum: Jurnal Pendidikan Islam, 2017)
Reaveling the marginalize of Islamic education, the developing proces of Islam education organization must be upheld. In this case the science of management is needed. Managing educational institutions of Islam means the process of institutional restructuring of Islamic education involving the human resources and non-human to raise a purpose of islam education efectively and efisienly. Talking about human resource management, the leadership becomes important factor to be used as a reference in institutional development. Transformative leadership can be an alternative method to lead an Islam education institution. Therefore, here where the function of the dimensions of the role of the concept is expected to provide a major influence in the leadership in Islamic Education Institution.